A study of port site infections in patients underwent laparoscopic cholecystectomy and its prevention and management - Biswas, Arnab; Nandy, Sagnik; Mondal, Debashis (International Journal of Research in Medical Sciences, 2023)
Background: Rapid growths in health care technology have given the surgeon the power of not only treating diseases surgically but also limiting surgical invasiveness. Methods: It is an institution based non-randomized, prospective, analytical study at Burdwan Medical College and Hospital. Results: As far as our study is concerned all the hospitals from where patients came were using “activated di-aldehyde” solution for sterilization of laparoscopic instruments; it may be a strong possibility that there might have been a growth of atypical mycobacteria in this solution, as four out of the five cases reported here found to be seropositive for tuberculosis. Conclusions: Port site infection (PSI), although infrequent, can be a frustrating complication in minimal access surgery (MAS), both for the patient as well as the operating surgeon. After the surgery, all the instruments should be dismantled completely. Cleaning and washing the instruments should be done under running water.